The incidence of secondary neoplasms in retinoblastoma survivors who underwent radiation therapy: A systematic review and meta-analysis - Anthea Casey; Julie Dewi Barliana (Taiwan Journal of Ophthalmology)
Secondary neoplasms are a significant cause of mortality among retinoblastoma survivors, particularly when exposed to radiation. This systematic review aims to investigate the association between radiation exposure and the incidence of secondary neoplasms in retinoblastoma survivors. A comprehensive literature search was conducted using PubMed, ProQuest, and EBSCOhost databases to gather relevant studies. Studies written in English about the incidence of secondary neoplasms in retinoblastoma patients who underwent radiotherapy were included. Retinoblastoma patients who did not receive radiotherapy were regarded as the control group. Studies involving animals and those without a control group were excluded. No date restrictions were applied. The last search was performed on April 6, 2022. The study selection process was presented in a flow diagram following the Preferred Reporting Items of Systematic reviews Meta-Analysis 2020 guidelines. The risk of bias was evaluated using the Risk of Bias in nonrandomized Studies of Interventions tool. Statistical analysis was performed using the Cochrane RevMan software (version 5.4.1). Five studies comprising a total of 3324 retinoblastoma patients were included. Of these, 290 (8.72%) patients developed secondary neoplasms, with 250 (86.21%) receiving radiotherapy. The results indicated that retinoblastoma patients who received radiotherapy had a higher risk of developing secondary neoplasms, with a pooled risk ratio of 5.12 (95% confidence interval 3.56–7.36, I2 = 14%). The findings of this review highlight the importance of considering the risk of developing secondary neoplasms when treating retinoblastoma. Regular medical surveillance for secondary neoplasms should be a standard part of care for retinoblastoma survivors, particularly those exposed to radiation.